Outcome of Repeat Venoarterial Extracorporeal Membrane Oxygenation in Postcardiotomy Cardiogenic Shock - Yusuff, Hakeem; Biancari, Fausto; Jónsson, Kristján; Ragnarsson, Sigurdur; Dalén, Magnus; Fux, Thomas; Dell'Aquila, Angelo M; Fiore, Antonio; Perna, Dario Di; Gatti, Giuseppe; Gabrielli, Marco; Juvonen, Tatu; et al. (Journal of cardiothoracic and vascular anesthesia, 2021)
OBJECTIVE: Data on patients requiring a second run of venoarterial extracorporeal membrane oxygenation (VA-ECMO) support in patients affected by postcardiotomy cardiogenic shock (PCS) are very limited. The authors aimed to investigate the effect of a second run of VA-ECMO on PCS patient survival. DESIGN: Retrospective analysis of an international registry. SETTING: Multicenter study, tertiary university hospitals. PARTICIPANTS: Data on adult PCS patients receiving a second run of VA-ECMO. MEASUREMENTS AND MAIN RESULTS: A total of 674 patients with a mean age of 62.9 ± 12.7 years were analyzed, and 21 (3.1%) patients had a second run of VA-ECMO. None of them required more than two VA-ECMO runs. The median duration of VA-ECMO therapy was 135 hours (interquartile range [IQR] 61-226) in patients who did not require a VA-ECMO rerun. In the rerun VA-ECMO group the median overall duration of VA-ECMO therapy was 183 hours (IQR 107-344), and the median duration of the first run was 114 hours (IQR 66-169). Nine (42.9%) of the patients who required a second run of VA-ECMO died during VA-ECMO therapy, whereas five (23.8%) survived to hospital discharge. No differences between patients treated with single or second VA-ECMO runs were observed in terms of hospital mortality and late survival. In patients requiring a second VA-ECMO run, the actuarial survival estimates at three and 12 months after VA-ECMO weaning were 23.8% ± 9.3% and 19.6% ± 6.4%, respectively. CONCLUSIONS: Repeat VA-ECMO therapy is a valid treatment strategy for PCS patients. Early and late survivals are similar between patients who have undergone a single or second run of VA-ECMO.
Keywords: Registries; complications; Humans; lidé středního věku; mimotělní membránová oxygenace; registrace; Shock, Cardiogenic; Aged; dospělí; výsledek terapie; multiple cannulation; senioři; lidé; kardiogenní šok; mortalita v nemocnicích; survival; Extracorporeal Membrane Oxygenation; Adult; extracorporeal membrane oxygenation; Middle Aged; Retrospective Studies; ECMO; Treatment Outcome; retrospektivní studie; Hospital Mortality; cardiac surgery